Biodiversitas udang pada ekosistem mangrove Teluk Awur, Jepara dan perbandingannya dengan beberapa kawasan ekosistem mangrove di Indonesia - T M Faisal; A Putriningtias; S Redjeki; R Pribadi; R Pratiwi; Helmy Akbar (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
The mangrove ecosystem area of ​​Teluk Awur, Jepara is a mangrove replant (MR) area. Compared to several other research sites in Indonesia, the Teluk Awur area has a relatively high shrimp biodiversity. Higher shrimp biodiversity was found in the mangrove replant (MR) area which had an older age. Shrimp biodiversity in Teluk Awur consists of 11 species of shrimp (crustacean, sub order Natantia) from 4 families: Alpheidae, Penaeidae, Mysidae and Palaemonidae. Shrimp biodiversity in other areas consists of 4-12 species from 2-4 families. It can be concluded that ecosystem restoration through mangrove replanting can restore the function of the mangrove ecosystem and provide living niches for organisms.